Optimisation of material and strengthening process in design for performance of elastic elements. (May 2015) - Yan, Z.; Tu, G.; Liu, M.
Abstract : Being a commonly used structural element, the elastic element should satisfy the requirements of deformation features under load and avoid wear failure, fracture fatigue and elastic extenuation. This study takes the Belleville spring as an example of an elastic element. The impact of material and strengthening process, including extrusion of rounded corners, shot peening and pre-stressing, on the product's property and reliability life (such as load deformation feature, fatigue fracture and elastic extenuation) have been investigated. A method of integrated product and process design for elastic elements has been established. Besides, the feasibility of the method has been tested using a practical example where the design requirements are satisfied by optimising the material and strengthening process, implying that the method can also be applied to other elastic elements.